More Than One-Third of Pregnant Women in Ethiopia Had Dropped Out From Their ANC Follow-Up: Evidence From the 2019 Ethiopia Mini Demographic and Health Survey - Tariku, Mandaras; Tusa, Biruk Shalmeno; Weldesenbet, Adisu Birhanu; Bahiru, Nebiyu; Enyew, Daniel Berhanie (Frontiers in Global Women's Health, 2022)
Background In Ethiopia, the magnitude of antenatal care (ANC) practice and institutional delivery is low as compared with developed countries. The majority of the pregnant women have not completed their ANC follow-up and only 43% of women have reached the four and above ANC. This study was conducted to determine the magnitude of ANC dropout and associated factors among pregnant women in Ethiopia. Methods Secondary data analysis was conducted using the 2019 Ethiopia Mini Demographic and Health Survey 2019 (2019 EMDHS). The sample was selected using a stratified, two-stage cluster sampling design and the data were analyzed using the binary logistic regression model to identify factors associated with ANC dropout. Adjusted odds ratio (AOR) with 95% CI was reported to declare significance and strength of association. A total weighted sample of 2,143 women who had antenatal care follow-up during pregnancy was included. In the multivariate logistic regression analysis, variables having a p-value < 0.05 were considered to have a significant association with ANC dropout. Result The magnitude of ANC dropout was 39.12% (95% CI: 37.07 and 41.20%) among women who had ANC follow-up in Ethiopia. Aged 30–49 years [AOR = 0.71; 95% CI: (0.54, 0.94)], attended primary [AOR = 0.79; 95% CI: (0.62, 0.99)], secondary [AOR = 0.63; 95% CI: (0.44, 0.87)], and higher education [AOR = 0.39; 95% CI: (0.25, 0.62)], were in first trimesters [AOR = 0.49; 95% CI: (0.40, 0.60)] at the time of first ANC visit, and had access to laboratory service [AOR = 0.25; 95% CI: (0.13, 0.51)] were found to be a negative significant associated factors of ANC dropouts, whereas being rural resident [AOR = 1.53; 95% CI: (1.11, 2.10)] has a positive significant association with ANC dropouts. Conclusion More than one-third of the pregnant women in Ethiopia had dropped out from their ANC follow-up in the study period. Being old-aged, educated, urban resident, having a first ANC visit in the first trimester, and having access to laboratory service were negatively associated with ANC dropouts. Therefore, we recommended encouraging women to have ANC visit at an early stage of pregnancy and conducting basic laboratory investigations during their visit. When undertaking that, due attention should be given to young, uneducated, and rural dweller women.